Tailoring the degradation and mechanical properties of poly(ε-caprolactone) incorporating functional ε-caprolactone-based copolymers. Issue 27 (10th June 2019) - Xu, Mi; Guo, Cuili; Dou, Haozhen; Zuo, Yi; Sun, Yawei; Zhang, Jinli; Li, Wei
Abstract : Functional block copolymers (COPs) were synthesized through the ring-opening polymerization, and the effects of COPs on the hydrolytic & oxidative degradation and mechanical properties of PCL/COP composites were studied. Abstract : A series of functional block copolymers (COPs) was synthesized through the ring-opening polymerization of ε-caprolactone (CL) and γ-(carbamic acid benzyl ester)-ε-caprolactone (CABCL) monomers at different ratios, and then the effects of the COP additives on the hydrolytic and oxidative degradation and mechanical properties of PCL/COP samples were studied. From characterization using DSC, POM, AFM, WAXD, SAXS, etc ., it was demonstrated that the content and distribution of pendant side chains in the COPs can alter the nucleation of macromolecular chains, and then modulate the lamellar thickness and crystallinity of the PCL/COP samples. Such variations of the macromolecular structures result in distinct changes in the mechanical properties during degradation. These results provide useful guidance for the development of ideal materials for biodegradable polymer stents with tunable degradation rates and the desirable evolution of the mechanical properties.